Optimising MSMEs B2B Marketing Performance Through Marketing Automation In CRM Strategy - Pitri Yanti; Ratih Hurriyati; Vanessa Gaffar; Puspo Dewi Dirgantari (Jurnal Manajemen, 2024)
This research investigates the influence of technology readiness and ICT capabilities on marketing automation within B2B MSMEs' CRM strategies. Using quantitative methods in 105 B2B MSMEs employing marketing automation tools, the study employs Structural Equation Modeling (SEM) with Lisrel 8.8 software for analysis. Findings reveal that Technology Readiness significantly impacts ICT Capability, with innovation indicators holding a dominant 67.240 per cent effect. ICT Capability positively influences marketing automation, primarily driven by the use of ICT (84.600 per cent). Marketing automation correlates positively with B2B CRM, notably through message reach (65.610 per cent). B2B CRM, in turn, significantly affects Marketing Performance, emphasising improved customer relationship quality (77.400 per cent) and expanded market influence (42.250 per cent). Notably, technology readiness does not directly impact marketing automation, necessitating ICT capability for practical implementation in customer relationship management. In conclusion, marketing automation enhances B2B MSMEs' marketing performance, contingent on their ICT capabilities, despite the importance of technology readiness.